The Effect of Periodicity, and Length and Depth of Freshening on the Yield of Resin from Pinus roxburghii - Rajkhowa, S.; Seth, S. K. (Indian Forester, 1961)
A set of three experimental plots maintained for 2 years at different localities at different altitudes, to study the effect of periodicity of freshening, and depth and height of the blaze, using standard 4" wide blazes, has shown that: (1) The periodicity of freshening exercises the maximum influence on the yield of resin per season. For the same depth of blaze and the same rise of the channel per season, increasing the number of equispaced freshenings per year increases resin yield upto 250% of that obtained under the standard 6 day cycle. A shorter tapping cycle tends to deepen the channels, but this tendency can be checked by freshening the upper 3" of the blaze alone instead of the upper 6" as practised now, at only a slight loss of yield, amounting to about 6%. (2) For the same freshening cycle, increasing the length of fresh wood removed at each freshening increased the yield. (3) The depth of freshening has no appreciable effect on resin yield. (4) Early start of tapping increases the yield of resin, not only by augmenting the annual yield by the extra amount collected during the early days, but also by increasing the yield in the subsequent month or so. (5) Under the prevailing prices, it is quite economical to tap as often as every alternate day without increasing the total height of the channel per year. How far such short cycles effect the health of the trees or jeopardise future yield has, however, to be investigated in long term experiments.